Deepfakes Technology Using Artificial Intelligence (International Journal of Innovative Research in Computer Science & Technology, 2022)
In spite of the fact that controls of visual  and hear-able media are just about as old as media  themselves, the new entry of deepfakes has denoted a  defining moment in the formation of phony substance.  Fueled by the most recent mechanical advances in manmade reasoning and artificial intelligence (AI), deep fakes offer computerized methods to make counterfeit substance  that is increasingly hard for human spectators to recognize.  The prospects to hoodwink are unending including  controlled pictures, recordings, and sound and associations  should be ready as this will without a doubt have a huge  cultural effect. In this article, I will cover working meaning  of deepfakes along with an outline of its fundamental  innovation. We order distinctive deepfake types and  distinguish dangers and freedoms to assist associations with  pondering the eventual fate of deepfakes. At last, I trust that  our general public can be more ready to counter deepfakes  as we appreciate deepfakes.
Keywords: (Artificial Intelligence) AI; Deep Fake; Neural Network